Technology and Policy Strategies for Enhancing Freshwater Fish Seed Production Capacity at the Regional Fish Hatchery (UPTD BBI) of Bontang City - Syamsu Wardi; Amrullah; Dahlia; Nursidi Latief; Muslimin Tompo (Universitas Islam Lamongan, 2026)
The production capacity of freshwater fish seeds at the Regional Fish Hatchery (UPTD BBI) of Bontang City has not met regional demand. This study aims to formulate technology and policy strategies to enhance freshwater fish seed production capacity. This study uses primary and secondary data to provide a comprehensive overview of freshwater fish seed production capacity at the Bontang City BBI Technical Implementation Unit. The research sample was selected using purposive sampling, comprising 30 internal respondents BBI and 7 relevant academic experts. A mixed-methods approach was applied, including SWOT analysis, IFE–EFE and IE matrices, and the Analytical Hierarchy Process (AHP). Results indicate that actual production of 173,840 seeds per year satisfies only approximately 14.5% of regional demand (±1,200,000 seeds/year), resulting in an 85.5% supply deficit. IFE (±2.40) and EFE (±2.00) scores place the organization in IE Quadrant V (hold and maintain). AHP results identify technology and production systems as the top priority (weight 0.30), followed by human resources and infrastructure (each 0.20). The integrated SWOT–AHP analysis prioritizes the WO strategy (global weight 0.38). Strengthening production systems, improving human resource capacity, and gradually upgrading infrastructure are recommended to increase seed production capacity and support regional food security